Pengaruh Financial Distress, Cash Holdings, dan Profitabilitas Terhadap Manajemen Laba dengan Syaria Supervisory Board sebagai Variabel Moderasi - Ajeng Suci Mawa Rindani; Zulfikar Zulfikar (Politeknik Ganesha Medan, 2025)
One of the goals of a company is to generate profits or large profits from the results of its operational activities, where a company can be considered good when the company can achieve and maximize its profits, profit management is one of the manager's choices in accounting policies to achieve some of its goals. Profit management can be done in the form of income increasing or income decreasing, depending on the needs and goals to be achieved. A company's profit management actions are carried out by way of income increasing or income decreasing, depending on the needs and goals to be achieved. n profit. This study aims to analyze the effect of financial distress, cash holding, and profitability on earnings management with the sharia supervisory board as a moderating variable. The population used is all sharia banking companies registered with the Financial Services Authority (OJK) for the period 2020 to 2023, totaling 33 companies. This study is a quantitative study through the use of secondary data. Using the purposive sampling method, namely sampling based on certain criteria so that 23 companies were obtained, and 92 samples for four years, with final data of 79 samples. Using multiple linear regression techniques and MRA. The results of the study show empirical evidence that profitability affects management earnings, the higher the profitability the lower the management earnings. The higher the profitability of the company, the more motivated it will be to present its actual financial statements without the need to practice earnings management. While the level of financial distress of a company does not affect earnings management. The condition of a company experiencing financial difficulties does not always encourage the company to carry out earnings management. Likewise, a company's cash holding has nothing to do with earnings management. In addition, the Sharia Supervisory Board as a moderating variable can moderate the effect of profitability on earnings management, weakening the effect of profitability on earnings management practices, because of the control and also sharia ethics that must be upheld by the company.